Analisis Minat Membaca Mahasswa Biologi dan Faktor Penyebabnya dalam Konteks Alam Sekitar Kampus UIR - Suryanti, Suryanti; Robiah, Siti; Ferazona, Sepita; Simatupang, Mona Kristina (UIR Press, 2026)
Interest in reading activities is a crucial foundation for the process of knowledge acquisition and learning, particularly within the scope of higher education. This study aims to analyze Biology students' reading interest and its contributing factors within the context of the natural environment of the UIR campus. The research employs a descriptive quantitative methodology. The population consists of all students in the Biology Study Program, totaling 160 individuals. A total sampling technique (saturated sample) was applied, where all members of the population served as research samples. The research instrument utilized a questionnaire, which underwent construct validation by peers. The questionnaire comprised 51 statements regarding reading interest and 59 statements regarding its contributing factors, using five-point scale options. Data collection was conducted via Google Form. The research results showed that the average score per sub-indicator for Biology students' reading interest was 73.03 (interested). Meanwhile, the average score for the indicators of factors influencing reading interest was 71.46 (not interested). It can be concluded that the overall reading interest of Biology students and its contributing factors within the context of the UIR campus environment reached a score of 72.24 (interested).